Analisa Kesesuaian Model Simulasi dari Simulator PyBaMM dengan Data Eksperimen pada Battery Lithium-ion - Kholifah, Nur; l, rohman; Rofi’i , Imam (PT. BERBAGI TEKNOLOGI SEMESTA, 2025)
Lithium-ion batteries are rechargeable energy storage devices that store and release energy by shuttling lithium ions between two electrodes with opposite polarities through an electrolyte. High-energy density lithium-ion batteries have been the subject of research, leading to the development of various lithium-ion battery systems, including battery modeling systems. PyBaMM (Python Battery Mathematical Modeling) is a software tool used for quickly and flexibly simulating battery models. The development of electrochemical battery modeling faces several challenges, with one of them being the complexity of the electrochemical battery system involving various chemical reactions and physical processes. Therefore, accurate and valid battery modeling is necessary to predict battery behavior under various operational conditions. This thesis aims to analyze the compatibility of battery simulation models within the PyBaMM simulator with experimental data from lithium-ion batteries. The objective is to gain a better understanding of how well the mathematical models in PyBaMM can represent the actual behavior of lithium-ion batteries. The compatibility analysis between the models and experimental data is performed using the Goodness of Fit Test with the Chi-Square (χ2) test method. The simulation result obtained in this research consists of voltage versus lithium-ion battery discharge time graphs that compare the PyBaMM simulator models with experimental data. There is no significant difference between the lithium-ion battery models generated from PyBaMM simulations and experimental data. The compatibility of the lithium-ion battery models produces from PyBaMM simulations with experimental data has an accuracy level of 97% - 99%.